ATP as Phosphorus and Nitrogen Source for Nutrient Uptake by Fagus sylvatica and Populus x canescens Roots - Scheerer, Ursula; Trube, Niclas; Netzer, Florian; Rennenberg, Heinz; Herschbach, Cornelia (Frontiers in Plant Science, 2019)
The present study elucidated whether roots of temperate forest trees can take up organic phosphorus in the form of ATP. Detached non-mycorrhizal roots of beech (Fagus sylvatica) and grey poplar (Populus x canescens) were exposed under controlled conditions to 33P-ATP and/or 13C/15N labelled ATP in the presence and absence of the acid phosphatase inhibitor MoO42-. Accumulation of the respective label in the roots was used to calculate 33P, 13C and 15N uptake rates in ATP equivalents for comparison reason. The present data shown that a significant part of ATP was cleaved outside the roots before phosphate (Pi) was taken up. Furthermore, nucleotide uptake seems more reasonable after cleavage of at least one Pi unit as ADP, AMP and/or as the nucleoside adenosine. Similar results were obtained when still attached mycorrhizal roots of adult beech trees and their natural regeneration of two forest stands were exposed to ATP in the presence or absence of MoO42-. Cleavage of Pi from ATP by enzymes commonly present in the rhizosphere, such as extracellular acid phosphatases, ecto-apyrase and/or nucleotidases, prior ADP/AMP/adenosine uptake is highly probable but depended on the soil type and the pH of the soil solution. Although uptake of ATP/ADP/AMP cannot be excluded, uptake of the nucleoside adenosine without breakdown into its constituents ribose and adenine is highly evident. Based on the 33P, 13C and 15N uptake rates calculated as equivalents of ATP the ‘pro and contra’ for the uptake of nucleotides and nucleosides is discussed.